Examining possible Relationships between mindfulness, stress, school and sport performances and athlete burnout - Moen, F.; Federici, R. A.; Abrahamsen, F. (International Journal of Coaching Science, 2015)
This article investigates the impact of mindfulness on stress, perceived performance in school and sports, and on athlete burnout. In the present investigation 483 Norwegian junior athletes from seven different schools for elite sports were invited to partake in an online survey of which 382 athletes responded (79%). The athletes were from different sports such as cross country skiing, Nordic combined, ski jumping, volleyball, handball, track and field, ice hockey, biathlon, cycling and orienteering. We tested whether mindfulness affected stress, perceived performance in school and sports, and athlete burnout utilizing structural equation modeling. As hypothesized, mindfulness was negatively related with stress and burnout, whereas stress was positively related with burnout and negatively related with perceived performances in school and sports. Mindfulness was positive related with perceived performances in sports and in school, whereas perceived performances in sports where negatively related with burnout. Hence, for this investigation it seemed that mindfulness was an important stress buffer and may help elite youth athletes to avoid burnout and perform better. The results are discussed in regard of applied implications and possible future research.